2007
DOI: 10.1158/0008-5472.can-07-0030
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-α–Mediated Regulation of Low-Density Lipoprotein Receptor–Related Protein and Urokinase Increases Astrocytoma Invasion

Abstract: Aggressive and infiltrative invasion is one of the hallmarks of glioblastoma. Low-density lipoprotein receptor-related protein (LRP) is expressed by glioblastoma, but the role of this receptor in astrocytic tumor invasion remains poorly understood. We show that activation of protein kinase C-A (PKC-A) phosphorylated and down-regulated LRP expression. Pretreatment of tumor cells with PKC inhibitors, phosphoinositide 3-kinase (PI3K) inhibitor, PKC-A small interfering RNA (siRNA), and short hairpin RNA abrogated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…We speculate that such a phenomenon was probably due to the impaired invasive ability of aQP4-reduced ln229 cells. similar to migration and adhesion, invasion through the extracellular matrix is an important step in tumor invasion (49). our Matrigel invasion assay demonstrated that reduction of aQP4 led to a decrease in invasiveness of the ln229 cells.…”
Section: Discussionmentioning
confidence: 61%
“…We speculate that such a phenomenon was probably due to the impaired invasive ability of aQP4-reduced ln229 cells. similar to migration and adhesion, invasion through the extracellular matrix is an important step in tumor invasion (49). our Matrigel invasion assay demonstrated that reduction of aQP4 led to a decrease in invasiveness of the ln229 cells.…”
Section: Discussionmentioning
confidence: 61%
“…There are many reports proving a close relationship between PKC expression and high invasion and migration of malignant glioma cells [200][201][202][203][204]. As mentioned above, translocation of PKC from the cytosolic fraction to the glioma cell membrane after TPA treatment increases ERK/NF-B-dependent MMP-9 activation and cell migration [200].…”
Section: Gastrointestinal Stromal Tumormentioning
confidence: 89%
“…As mentioned above, translocation of PKC from the cytosolic fraction to the glioma cell membrane after TPA treatment increases ERK/NF-B-dependent MMP-9 activation and cell migration [200]. PKC -induced phosphorylation and downregulation of low-density lipoprotein receptor-related protein stimulate the secretion of uPA and the invasion of glioma cells into the surrounding normal brain tissue [201]. Furthermore, invasion and migration of glioma cells involve several signaling pathways such as PKC -mediated N-cadherin cleavage [202], increased motility by PKC -mediated NG2 phosphorylation at Thr-2256 [203], and PKC or /SRF-mediated RTVP-1 expression [204].…”
Section: Gastrointestinal Stromal Tumormentioning
confidence: 94%
“…Therefore the effect of TNF-α appears to be coupled to atypical PKC activation in human dental pulp cells. Currently, the involvement of PKCα in the up-regulation of uPA has been demonstrated [25,26]. Therefore PKCα may be a candidate for the effect of PMA in uPA secretion in human dental pulp cells.…”
Section: Resultsmentioning
confidence: 99%